2020
DOI: 10.1002/dc.24519
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic inflammatory mass associated with sodium polystyrene sulfonate crystals diagnosed by endoscopic ultrasound‐guided fine needle aspiration cytology

Abstract: Surgical pathologists, especially those with subspecialty expertise in gastroenterological pathology, are by now relatively familiar with sodium polystyrene sulfonate (SPS) (Kayexalate, Concordia International Corp, Oakville, Ontario, Canada)-associated gastrointestinal tract injury. 1 In surgical pathology specimens, SPS typically presents as crystalline structures with a fish scale (FS) appearance. 2 To the best of our knowledge, the cytological morphology of SPS has not been previously described and there h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…All of the above-mentioned studies show the high diagnostic value of EUS-FNA for pelvic metastases. Another study reported the diagnosis of a sodium polystyrene sulfonate crystal-induced pelvic inflammatory mass using EUS-FNA ( 22 ). In the present study, EUS-FNA diagnosed 2 females with pelvic inflammatory masses, both of whom were asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…All of the above-mentioned studies show the high diagnostic value of EUS-FNA for pelvic metastases. Another study reported the diagnosis of a sodium polystyrene sulfonate crystal-induced pelvic inflammatory mass using EUS-FNA ( 22 ). In the present study, EUS-FNA diagnosed 2 females with pelvic inflammatory masses, both of whom were asymptomatic.…”
Section: Discussionmentioning
confidence: 99%